Caring for Thirst: Challenges to Access to Water in Slovakia through a Legal Lens - Adam Máčaj; Maroš Matiaško (Critical Romani Studies)
This article provides an assessment of segregated Romani communities’ access to water in Slovakia. It combines philosophical and human rights perspectives and focuses on obstacles communities encounter when pursuing access to safe drinking water through the context of law, whether national legislation, EU legislation, or international human rights. This article aims to establish the case of racial discrimination against Roma in Slovakia through the lens of the environmental justice and especially water precarity. This contribution also explores international standards concerning the right to access water from the perspective of vulnerability, arguing that specific populations living in precarious situations should have an unconditional right to water.